Pengaruh Brand Image, Harga Dan Promosi Terhadap Keputusan Pembelian Sepeda Motor Yamaha Pada Sentral Yamaha Medan - Gurning, Sara; Sembiring, Rasmulia; Nadapdap, Kristanty Marina Natalia (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
This study aims to examine and analyze the influence of brand image, price, and promotion on the decision to purchase Yamaha motorcycles at Sentral Yamaha Medan. The research method used is a quantitative descriptive method. The population in this study consisted of 82 consumers in 2024, and the sample was also 82 consumers, using a saturated sampling technique. The data analysis method employed is multiple linear regression analysis. Based on the results of the t-test for partial hypotheses, it can be concluded that brand image has a positive and significant effect on purchase decisions, price has a positive and significant effect on purchase decisions, and promotion also has a positive and significant effect on purchase decisions. Furthermore, based on the F-test for the overall hypothesis, it can be concluded that brand image, price, and promotion simultaneously have a positive and significant effect on purchase decisions. The coefficient of determination (Adjusted R Square) is 0.730 or 73%, meaning that 73% of the influence on purchase decisions is explained by product knowledge, product quality, service quality, and price, while the remaining 27% is influenced by other variables or factors.